Mineralogy and geotechnical properties of alkaline-activated kaolin with zeolitic tuff and cement kiln dust as landfill liners - Shaqour, Fathi (Frontiers in Materials, 2024)
Mixtures of variable proportions of kaolin, quartz sand, zeolitic tuff, and cement kiln dust were blended while adding an 8 M sodium hydroxide (NaOH) solution to allow alkali-activation of kaolin and achieve the optimum strength. This study investigated the mineralogy, microstructure, and geotechnical properties of the prepared mixtures. The aim was to produce a sustainable, environmentally friendly landfill liner. The samples were compacted in stainless steel molds to a maximum dry density and optimum moisture content, extruded from the molds, and left to cure in an oven at varying temperatures from 40 °C to 80 °C for 24 hours. The investigations included XRD, SEM, unconfined compressive strength, and hydraulic conductivity tests. Test results showed the development of a hydroxysodalite binder due to the alkali reaction of kaolin, which caused an increase in strength ranging from 20 to 25 MPa depending on the curing temperature. Alkaline activation was effective even at temperatures as low as 40 °C. A mixture of 100 units of kaolin, 45 units of sand, 45 units of zeolitic tuff, and 10% by weight cement kiln dust (CKD) with an 8 M sodium hydroxide activator was found to best achieve the required strength and hydraulic conductivity of 10-9 m/s for the landfill liner. The zeolitic tuff with high cation exchange capacity, available in the mixture, absorbs contaminants in the leachate and prevents pollution of the groundwater. The use of cement kiln dust contributes to enhancing strength and solving an acute environmental problem.